Resilience in older adults with cancer: A scoping literature review. Issue 1 (January 2023) - George, Thomas; Shah, Farah; Tiwari, Abhay; Gutierrez, Eutiquio; Ji, Jingran; Kuchel, George A.; Cohen, Harvey J.; Sedrak, Mina S.
Abstract: Introduction: Resilience, the ability to respond to stressors by maintaining or rapidly returning to normal homeostasis, serves as a new paradigm to improve the care of older adults. However, resilience research in oncology is nascent. We aimed to describe the current research landscape on physical, cognitive, and psychosocial resilience in older cancer patients. Materials and Methods: We searched PubMed/MEDLINE from inception to January 28, 2022 for records with the terms "resilient OR resilience OR resiliency." We included studies that focused on persons over age 65 with cancer and assessed physical, cognitive, or psychological resilience. We excluded studies that did not report original data; did not have the full text available; assessed resilience on fewer than three time points; and published in non-English languages. Definitions and measures of resilience were extracted and categorized using qualitative analysis. Results: Of 473 articles screened, we found 29 articles that met criteria for inclusion in our review. There was a high degree of heterogeneity in the definitions and measures of resilience. Resilience was defined as robustness/resistance to decline ( n = 11), recovery from trauma/stressor ( n = 7), and adaptive and proactive coping behaviors ( n = 6). Ten papers did not define resilience. 21 studies utilized longitudinal analysis, five studies used randomized and nonrandomized control trials, and four studies assessed pre-post analysis. Stressors included cancer diagnosis ( n = 18), chemotherapy ( n = 3), radiation (n = 3), acute illness (n = 3), surgery ( n = 2), and hematopoietic cell transplant (n = 1). Discussion: Evidence for predictors and determinants of resilience in older adults with cancer is limited by the absence of standardized definitions and measurements. There is a fundamental need for a more precise definition, measures, and understanding of the physiologic mechanisms underlying the response to the physical, cognitive, and psychosocial stressors of cancer and its treatments.